Assessment of Evidence Regarding Minimally Invasive Surgery vs. Conservative Treatment on Intracerebral Hemorrhage: A Trial Sequential Analysis of Randomized Controlled Trials - Zhou, Xiang; Xie, Li; Altinel, Yuksel; Qiao, Nidan (Frontiers in Neurology, 2020)
Introduction The recent publication of a trial failed to prove the efficacy of minimally invasive surgery (MIS) in patients with intracerebral hemorrhage. The aim of this study was to answer the question that do we need more trials to compare MIS versus conservative treatment in these patients. Methods Databases were searched for relevant randomized trials on MIS (endoscopic surgery or stereotactic evacuation) versus conservative treatment. The primary outcome was significant neurological debilitation or death at the follow-up, and the secondary outcome was death. Both conventional meta-analysis and trial sequential analysis (TSA) were performed. Results Twelve trials with 2049 patients were included. In the conventional meta-analysis, the risk ratio of MIS versus conservative treatment were 0.82 (95%CI, 0.72-0.94) and 0.74 (95%CI, 0.62-0.88) for the primary and secondary outcome, respectively. In TSA, the cumulative z curve crossed the superiority boundary, which confirmed an 18.8% relative risk reduction of MIS versus conservative treatment for the primary outcome. It was also highly likely that MIS would reduce mortality by 24.3%. Several sensitivity analyses suggested the robustness of our results, including different prior settings, only including trials with blind outcome assessment and the assumption of future trials to be futile. Conclusions MIS seems to be more effective than conservative treatment in patients with intracerebral hemorrhage in reducing both morbidity and mortality. Repeating a clinical trial with similar devices, design and outcomes is unlikely to change the current evidence.